Impact of the Popular and Solidarity Economy in the RuralParish of Rumipamba - Loachmín, Mónica (2025)
Rural communities in Ecuador have historically been marginalizedand disadvantaged in terms of access to resources and economic opportunities. However, in recent years, interest and promotion of the Popular and Solidarity Economy (EPS) has increased as a way to improve living conditions and sustainable development in these commu-nities. This article explores the impact of the EPS in the rural parish of Rumipamba - Ecuador, highlighting its role in improving quality of life, promoting community participation and strengthening social andeconomic networks. A diagnosis and data collection of the Popular and Solidarity Economy and its effect on economic development was carried out, which will be taken as a case study of the survey of the Rural Parish of Rumipamba. It will focus on descriptive statistics, building a diagnosis of the study population that is in the economic range of the effect of tourism and its impact on the economy and improvement of thequality of life. Which there is a statistical analysis and application of policies related to the popular and solidarity economy.